Comparison of different methods to characterise the abrasivity potential and mechanical properties of carbonates with respect to its relevance for practical purposes in excavation technologies. Issue 1 (1st January 2023) - Aderhold, M; Disselkamp, C; Formanski, R; Grimberg, M; Grineisen, A M; Kroenert, L M; Ogan, M S; Romahn, H; Sandkühler, R; Skonetzki, C; Ullah, F; Zinke, B H; et al.
Abstract: The characterisation of the abrasivity potential of carbonates plays an important role for drilling-based excavation technologies, for example in tunneling or geothermal exploration. Although carbonates are known to have a rather low abrasivity, they have been associated with severe excavation performance reductions. We compared different methods to characterise the abrasivity potential of carbonates with respect to its applicability for practical purposes in excavation technologies. In this study, seven carbonate rocks were investigated which differ with respect to their microstructural properties and degrees of dolomitisation. These carbonate rock samples were selected from different lithological units in Germany (Jurassic: Kelheimer limestone, Wachenzell dolomite, Solnhofen limestone, Pappenheim limestone, Treuchtlingen limestone; Devonian: Wülfrath limestone, Brilon limestone). Rock samples were characterised with respect to basic physical properties (density, ultrasound velocity), microstructure (thin section analysis, XRD), mechanical properties (uniaxial compressive strength UCS, splitting tensile strength STS) and commonly applied abrasivity indices (Cerchar abrasivity index test CAI, LCPC test) as well as derived indices (equivalent quartz content eQu). Our results confirm that the tested carbonate rocks show low abrasivity indices in terms of CAI, LCPC and eQu with an increase in abrasivity potential with increasing dolomite content. The microstructural properties play an important role for the abrasiveness of purely calcitic carbonates. Uniaxial compressive strength and splitting tensile strength were high and can additionally be, as has been shown before, particularly sensitive to sample preparation. We conclude that carefully determining the mechanical properties of carbonate rock samples in combination with common approaches to determine the abrasivity potential is key to properly predict tool wear, and required to derive information on performance in carbonate rocks. This study is the outcome of a research-oriented teaching program at Ruhr-University Bochum within the Geoscience curriculum for students with focus on Engineering Geology. Student authors are listed in alphabetical order (Aderhold to Zinke).